GENE-07. LIQUID BIOPSY DETECTION OF GENOMIC ALTERATIONS IN PEDIATRIC BRAIN TUMORS FROM CELL-FREE DNA IN PERIPHERAL BLOOD, CSF, AND URINE. (23rd April 2019) - Pagès, Mélanie; Rotem, Denisse; Gydush, Gregory; Reed, Sarah; Rhoades, Justin; Ha, Gavin; Lo, Chris; Tracy, Adam; Jones, Robert; Becker, Sarah; Haller, Michaela; Chi, Susan; et al.
Abstract: Brain tumors require invasive neurosurgical procedures for diagnosis and tissue acquisition to guide precision medicine. Detection of tumor-derived cell-free DNA (ctDNA) would facilitate tumor profiling without risk of surgery-related morbidity. We aimed to validate a sample collection procedure and develop methodologies to detect ctDNA in CSF, plasma and urine from children with brain tumors. We prospectively collected blood, urine and CSF samples from 268 patients across all histological subtypes. We optimized a method to process ctDNA and performed ultra-low pass whole-genome sequencing (ULP-WGS) on 435 samples from 240 patients, confirming we could reliably construct sequencing libraries. ULP-WGS was used to assess copy number variations (CNVs) and tumor fraction, showing that the majority of samples exhibited no CNV, consistent with either absence in the tumor or low ctDNA level. We developed a pediatric brain tumor hybrid-capture sequencing panel, allowing identification of specific mutations/fusions with 80% sensitivity and 100% specificity at 10, 000X depth-sequencing. Comparing sequencing results from ctDNA samples to matched tumors and germline samples confirmed levels of ctDNA that were often too low for informative tumor profiling. The results from this large series provide insights regarding the limits of ctDNA assays to guide clinical care in pediatric brain tumors, across different tumor subtypes.